2018
DOI: 10.1177/0042098017740246
|View full text |Cite
|
Sign up to set email alerts
|

‘Nice apartments, no jobs’: How former villagers experienced displacement and resettlement in the western suburbs of Shanghai

Abstract: In this paper, we document the displacement and resettlement of over 11,000 villagers who were removed from their homes and relocated in modern apartment blocks to make way for the construction of a new business district in the western suburbs of Shanghai. We examine the expectations and concerns of displaced residents before and after their relocation. Our findings showed that while the former villagers recognized the improvement in their physical surroundings, they were deeply concerned about their loss of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 30 publications
0
51
1
1
Order By: Relevance
“…The relocation of millions of residents and forced evictions have been highlighted by many studies as major social problems of China’s mega developments (Hsing ; Jiang et al ; Shin ; Zhang , ). However, through the case of Neighbourhood No.57, we find that the biggest social problem in Lingang is in‐situ marginalisation whereby residents, who have not been relocated, suffer from declining public services and environmental quality due to nearby industrial activities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The relocation of millions of residents and forced evictions have been highlighted by many studies as major social problems of China’s mega developments (Hsing ; Jiang et al ; Shin ; Zhang , ). However, through the case of Neighbourhood No.57, we find that the biggest social problem in Lingang is in‐situ marginalisation whereby residents, who have not been relocated, suffer from declining public services and environmental quality due to nearby industrial activities.…”
Section: Resultsmentioning
confidence: 99%
“…However, the experience of relocation in peri‐urban areas has been more mixed. Studies found both negative experiences of displacement and residents complaining about the lack of employment (Jiang et al ) and more positive responses about improved living standards (Li and Song ). Hsing’s () research in rural Beijing revealed that the government is much keener to develop in the rural areas of cities.…”
Section: The Social Impact Of Mega Urban Projectsmentioning
confidence: 99%
See 3 more Smart Citations